2014
DOI: 10.1542/peds.2013-1872
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Course and Complications Associated With Home Oxygen Therapy for Mild Bronchiolitis

Abstract: BACKGROUND: Home oxygen has been incorporated into the emergency department management of bronchiolitis in high-altitude settings. However, the outpatient course on oxygen therapy and factors associated with subsequent admission have not been fully defined. METHODS: We conducted a retrospective cohort study in consecutive patients discharged on home oxygen from the pediatric emergency department at Denver Health Medical Cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 24 publications
3
18
1
Order By: Relevance
“…118,119 Most of the studies have been performed in areas of higher altitude, where prolonged hypoxemia is a prime determinant of LOS in the hospital. 120,121 Readmission rates may be moderately higher in patients discharged with home oxygen; however, overall hospital use may be reduced, 122 although not in all settings. 123 Concerns have been raised that home pulse oximetry may complicate care or confuse families.…”
Section: Action Statement Profile Kas 6bmentioning
confidence: 99%
“…118,119 Most of the studies have been performed in areas of higher altitude, where prolonged hypoxemia is a prime determinant of LOS in the hospital. 120,121 Readmission rates may be moderately higher in patients discharged with home oxygen; however, overall hospital use may be reduced, 122 although not in all settings. 123 Concerns have been raised that home pulse oximetry may complicate care or confuse families.…”
Section: Action Statement Profile Kas 6bmentioning
confidence: 99%
“…We question the use of cough as an outcome. Cough has not been shown to contribute to readmission rates in children with acute bronchiolitis discharged on home oxygen and has not been identified as a barrier to discharge in patients with bronchiolitis including those with an oxygen requirement . The secondary outcomes in this study (time to normal feeding and time to fit for discharge) are more clinically relevant.…”
mentioning
confidence: 89%
“…We question the use of cough as an outcome. Cough has not been shown to contribute to readmission rates in children with acute bronchiolitis discharged on home oxygen 2 and has not been identified as a barrier to discharge in patients with bronchiolitis including those with an oxygen requirement. 3 The secondary outcomes in this study (time to normal feeding and time to fit for discharge) are more clinically relevant.…”
Section: Referencesmentioning
confidence: 99%
“…Shah et al 1 recently published a study on the long term outcomes for infants with Apgar scores of 0 at 10 minutes and concluded that longterm outcomes for survivors may not be universally poor as suggested by previous studies. 2 The decision to stop resuscitation can be very challenging even for experienced paediatricians. The major clinical question is what proportion of these infants survive without major neurological sequelae if resuscitation proceeds beyond the 10 minutes advised by the Australian Resuscitation Council.…”
mentioning
confidence: 99%